Profiling of the Microbiome Associated With Nitrogen Removal During Vermifiltration of Wastewater From a Commercial Dairy - Lai, Ellen; Hess, Matthias; Mitloehner, Frank M. (Frontiers in Microbiology, 2018)
Vermifiltration is a biological treatment process during which earthworms (e.g. Eisenia fetida) and microorganisms reduce the organic load of wastewater. To infer microbial pathways responsible for nutrient conversion, past studies characterized the microbiota in vermifilters and suggested that nitrifying and denitrifying bacteria play a significant role during this wastewater treatment process. In contrast to previous studies, which were limited by low-resolution sequencing methods, the work presented here utilized next generation sequencing to survey in greater detail the microbiota of wastewater from a commercial dairy during various stages of vermifiltration. To complement sequence analysis, nitrogenous compounds in and gaseous emissions from the wastewater were measured. Analysis of 16S rRNA gene profiles from untreated wastewater, vermifilter influent, and vermifilter effluent suggested that members of Comamonadaceae, a family of the Betaproteobacteria involved in denitrification, increased in abundance during the vermifiltration process. Subsequent functional gene analysis indicated an increased abundance of nitrification genes in the effluent and suggested that the nitrogen removal during vermifiltration is due to the microbial conversion of ammonia. A finding that was also supported by the water chemistry and emission data. This study demonstrates that microbial communities are the main drivers behind reducing the nitrogen load of dairy wastewater during vermifiltration, providing a valuable knowledge framework for more sustainable and economical wastewater management strategies for commercial dairies.